2015
DOI: 10.5937/str1504028b
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic properties of carboxyl-terminated (butadiene-co-acrylonitrile)-based composite rocket propellant containing tris (2,3-epoxypropyl) isocyanurate as bonding agent

Abstract: ). The dynamic mechanical analysis showed that the tris(2,3-epoxypropyl) isocyanurate content did not affect the glass transition temperature of the tested propellants

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…The results are reported in our previous papers [6][7][8][9]. Regarding the loss factor evolution according to the temperature, it was observed that all the tested materials have shown two relaxation processes.…”
Section: E a (Wlf) -Activation Energy Of Viscoelastic Relaxation Basesupporting
confidence: 65%
See 3 more Smart Citations
“…The results are reported in our previous papers [6][7][8][9]. Regarding the loss factor evolution according to the temperature, it was observed that all the tested materials have shown two relaxation processes.…”
Section: E a (Wlf) -Activation Energy Of Viscoelastic Relaxation Basesupporting
confidence: 65%
“…At the maximum intensity of the tan(δ), the molecular rearrangement process from glassy to rubbery and vice versa is at its maximum. These values were reported in our previous paper [9].…”
Section: Dynamic Mechanical Thermal Analysis (Dmta)mentioning
confidence: 48%
See 2 more Smart Citations